Pengembangan Sistem Informasi Laporan Praktik Kerja Lapangan Mahasiswa Berbasis Web Menggunakan Metode Waterfall di Universitas Alwashliyah Labuhanbatu - Abdul Hakim Dalimunthe; Selamat Subagio; Samsir (CSRID (Computer Science Research and Its Development Journal), 2026)
The management of Field Work Practice (PKL) reports at the Faculty of Computer Science, Alwashliyah University (UNIVA) Labuhanbatu, is currently handled manually, leading to various issues such as delayed report submissions, document archiving difficulties, ineffective supervision monitoring, and slow grading processes by supervisors. This research aims to develop a web-based PKL report information system capable of centrally integrating administrative processes—ranging from student data management, placement, and report uploading to supervision monitoring and grading. The system was developed using the Waterfall method, comprising stages for requirements analysis, system design, implementation, testing, and maintenance. It was built using PHP, MySQL, and the Bootstrap framework. System testing employed the Black Box Testing method across 25 scenarios covering user authentication, management of student, lecturer, and industry partner (DU/DI) data, report uploads, the supervision process, and grading. Test results demonstrated that all scenarios executed successfully according to functional requirements, achieving a 100% success rate. Implementing this system improves the efficiency of PKL administration, accelerates information exchange among students, supervisors, and administrators, and results in report archiving that is more structured, well-documented, and accessible compared to the manual process.